Police Powers in Canada : the Evolution and Practice of Authority. - Macleod, R. C. (University of Toronto Press, 1994)
In their introduction, the editors point out that constitutional order is tied to the exercise of power by law enforcement agencies, and that if relations between the police and civil society continue to erode, the exercise of force will rise - a dangerous prospect for democratic societies.